Effect of Price and Service Quality on Customer Satisfaction and Its Implications for Customer Loyalty at Aston Pluit Hotel & Residence Jakarta - Jaya Saputra, Arfin; Djumarno, Djumarno (Dinasti International Journal of Economics, Finance & Accounting, 2021)
As a provider of lodging, Aston Pluit Hotel & Residence Jakarta ”always strives to improve customer satisfaction or hotel guests in order to maintain customer loyalty to Aston Pluit Hotel & Residence Jakarta itself. However, the problem related to this research is about customer loyalty to Aston Pluit Hotel & Residence Jakarta during the 2015-2018 period, during which the number of guests staying at the Hotel Pluit Aston & Residence Jakarta decreased significantly even though the Hotel Pluit Aston & Residence Jakarta raises service standards and promotions to attract guests to visit and stay at the hotel. This research is categorized in Explanatory Research, with the data survey method using a questionnaire. The sampling technique uses Probability Sampling for population withdrawal using census techniques, the sample of respondents is hotel guests with a total of 359 guests. The method used in this research is the analysis of Structural Equation Modeling (SEM) using the LISREL 8.8 program with a factor loading value of 0.05. The results of this study indicate a positive and significant effect of price on customer satisfaction, a positive and significant effect of service quality on customer satisfaction, a positive and significant effect of price on customer loyalty, a positive and significant effect of service quality on loyalty. customers, there is a positive and significant influence of customer satisfaction variables on customer loyalty. There is a positive and significant effect of both price and service quality on customer loyalty through customer satisfaction